2017
DOI: 10.4103/neuroindia.ni_220_17
|View full text |Cite
|
Sign up to set email alerts
|

Dose fractionated gamma knife radiosurgery for large arteriovenous malformations on daily or alternate day schedule outside the linear quadratic model: Proof of concept and early results. A substitute to volume fractionation

Abstract: DFGKRS is feasible for large AVMs with a fair nidus obliteration rate and acceptable toxicity. Cumulative prescription dose seems to be the most significant independent predictor for outcome following DFGKRS with 29-30 Gy resulting in a fair nidus obliteration with least adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Mukherjee et al have shown in their study that DFGKRS on a daily schedule in cases of large AVM have shown excellent obliteration rates with acceptable toxicity. 5 A similar protocol was used in our patient, and there was marked a reduction in the size of nidus as compared to baseline. The patient however presented with rebleed due to associated AVF which was unmasked as nidus was obliterated.…”
Section: Case P R E S E N Tat I O Nmentioning
confidence: 77%
“…Mukherjee et al have shown in their study that DFGKRS on a daily schedule in cases of large AVM have shown excellent obliteration rates with acceptable toxicity. 5 A similar protocol was used in our patient, and there was marked a reduction in the size of nidus as compared to baseline. The patient however presented with rebleed due to associated AVF which was unmasked as nidus was obliterated.…”
Section: Case P R E S E N Tat I O Nmentioning
confidence: 77%
“…Since the introduction of radiosurgery for AVM, neurosurgical and radiosurgical communities remained curiously enthusiastic to expand the horizon of radiosurgery by targeting other vascular anomalies such as cavernous malformations, fistulas, and now aneurysms. Unfortunately, the spectacular success with AVM could not be reproduced with other intracranial vascular pathologies [2,3]. Among all vascular anomalies, aneurysm is considered to be the most ferocious and morbid condition with the potential of significant chances of rebleeding and complications including high rates of death.…”
Section: Doi: 101159/000517106mentioning
confidence: 99%
“…SRS, which can be performed using Linac, Cyberknife, and gamma knife (GK), is preferred for small lesions and is usually performed in a single session compared to conventional radiation therapy. An excellent tumor control rate and significant treatment efficacy have been reported for many intracranial tumors treated by radiosurgery [1][2][3]. Gamma knife radiosurgery (GKRS) is superior to other SRS methods in steep dose gradients and high-dose conformity, which is essential for excellent target coverage and vital structure sparing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some indications for treatment with fractionated GKRS include benign peri-optic nerve tumors, tumors 10 cc in volume, and re-irradiation of tumors previously treated with SRS [ 7 , 8 ]. Using fractionated GKRS, the therapeutic benefit was increased, and complications were reduced; simultaneously [ 1 , 3 ]. On the other hand, in GKRS dose inhomogeneity can be obtained so that the received dose to the central portion of the tumor is twice as high as that of the periphery of the tumor.…”
Section: Introductionmentioning
confidence: 99%